Цилиндрические гармоники магнитного поля однородно намагниченного цилиндра - Гетьман, А.В.; Константинов, А.В. (Електротехніка і електромеханіка, 2011)
Application of cylindrical harmonics apparatus to magnetic field of a uniformly magnetized cylinder is considered. Results are obtained under utilization of two magnetized cylinder models: one based on fictitious magnetic charges and the other based on spatial distribution of magnetic dipoles.